Shared Decision-Making and Information Needs among People with Generalized Anxiety Disorder - Vanesa Ramos-García; Amado Rivero-Santana; Andrea Duarte-Díaz; Lilisbeth Perestelo-Pérez; Wenceslao Peñate-Castro; Yolanda Álvarez-Pérez; Ana Isabel González-González; Pedro Serrano-Aguilar (MDPI AG, 2021)
Shared decision making (SDM) aims to involve patients in the decisions about their care, considering their preferences, values and concerns about the different treatment options. However, research shows that people with mental health problems have considerable unmet information needs about their condition. This community-based cross-sectional study explores the SDM process and information needs among people with Generalized Anxiety Disorder (GAD), as an initial step in the design and development of a Patient Decision Aid for this population. Seventy participants completed an online survey with the Control Preference Scale, and questions about the perceived difficulty of past treatment decisions and the use of the Internet for searching for GAD-related information. Most participants preferred an active (42.9%) or collaborative role (41.4%) in the SDM process, and 53% did not perceive their preferred role. Information provided by healthcare professionals was considered insufficient by 28% of the sample, and over 30% reported using the Internet to look for GAD-related information at least once a week or more. The most relevant GAD-related information needs were general information (71.4%), information on self-help groups (65.7%), recommendations on how to face this disorder (61.4%) and information on treatment options (50%). Exploratory analyses showed that patients who perceived an active participation were more likely to search for information frequently (p = 0.038), and those who felt more involved than desired tended to search for more themes (p = 0.049). In summary, the study showed that a considerable percentage of GAD patients have unmet needs related to decision-making participation and information.